Building peace through education in the Democratic Republic of the Congo - Rita Locatelli (University of Bologna, 2023)
The education system of the Democratic Republic of the Congo (DRC) is facing multiple challenges that are related to the situation of severe poverty affecting the population, the lack of public funding, the low quality of learning, class overcrowding and high illiteracy rates. The situation is worsened and at the same time caused by the situation of ongoing armed conflict and violence which have been affecting the country since its independence. While the connections between education and conflict are often difficult to disentangle, education can play a key role in creating a more equitable system where peace and inclusion are favoured, thus protecting the most vulnerable. According to latest available estimates, however, the promotion of peace and citizenship education programmes and manuals remains still a challenge in the DRC. The paper presents the Maison de paix experience - a project of international cooperation in the field of education promoted by an Italian association in Kikwit, in the western region of the DRC. It underlines the important role of participatory educational governance and teacher training, as a way to promote justice, solidarity and inclusion which are fundamental values in peace education.